Multiscale methods for oil reservoir simulation - Guiraldello, Rafael Trevisanuto (2019)
In this thesis a multiscale mixed method aiming at the accurate approximation of velocity and pressure fields in heterogeneous porous media is proposed, the Multiscale Robin Coupled Method (MRCM). The procedure is based on a new domain decomposition method in which the local problems are subject to Robin boundary conditions. The method allows for the independent definition of interface spaces for pressure and flux over the skeleton of the decomposition that can be chosen with great flexibility to accommodate local features of the underlying permeability fields. Numerical simulations are presented aiming at illustrating several features of the new method. We illustrate the possibility to recover the multiscale solution of two wellknown methods of the literature, namely, the Multiscale Mortar Mixed Finite Element Method (MMMFEM) and the Multiscale Hybrid-Mixed (MHM) Finite Element Method by suitable choices of the parameter b in the Robin interface conditions. Results show that the accuracy of the MRCM depends on the choice of this algorithmic parameter as well as on the choice of the interface spaces. An extensive numerical assessment of the MRCM is conduct with two types of interface spaces, the usual piecewise polynomial spaces and the informed spaces, the latter obtained from sets of snapshots by dimensionality reduction. Different distributions of the unknowns between pressure and flux are explored. The results show that b, suitably nondimensionalized, can be fixed to unity to avoid any indeterminacy in the method. Further, with both types of spaces, it is observed that a balanced distribution of the interface unknowns between pressure and flux renders the MRCM quite attractive both in accuracy and in computational cost, competitive with other multiscale methods from the literature. The MRCM solutions are in general only global conservative. Two postprocessing procedures are proposed to recover local conservation of the multiscale velocity fields. We investigate the applicability of such methods in highly heterogeneous permeability fields in modeling the contaminant transport in the subsurface. These methods are compared to a standard procedure. Results indicate that the proposed methods have the potential to produce more accurate results than the standard method with similar or reduced computational cost.